Screening Of Novice Adolescent Girls for Anemia Studying in Medical and Paramedical Colleges at Civil Hospital Campus, Ahmedabad, Gujarat, India - Chavada, Mallika V; Prajapati, Jagruti D; Rathod, Dinesh M; Chaudhary, Pooja; Agrawal, Kriti M (National Journal of Community Medicine, 2013)
Introduction: Anemia is major public health problem in adolescents in India. This study was conducted to estimate the prevalence of anemia among novice medical and paramedical adolescent girls students and to study the socio-demographic factors associated with anemia in them. Methods: This cross-sectional study was conducted by purposive non random sampling method in March 2011. Data was collected from 357 novice girl students of four medical and paramedical colleges and one nursing school in civil hospital campus Ahmedabad, Gujarat, India. Statistical analysis was done by Chi-square test and Z test. Results: In present study, anemia was found in 43.52% girls. A significantly more girls were anemic in Physiotherapy College (58.2%) and Nursing College (53.2%) compared to other colleges. Anemia was more prevalent in the girls (61%) who had heavy menstrual bleeding and who resided (48.1%) in the hostel. Mean BMI of anemic girls was significantly less as compared to non anemic girls. Conclusion: Association of anemia with academic course, hostel staying, previous operation/hospitalization and heavy menstruation was significant.